NUMERICAL VS. PHYSIQUE OF A CHILD: A SEARCH FOR CONCURRENCE AGE OF MARRIAGE BETWEEN THE SHARIAH AND NIGERIAN LAW - Abolaji, Abdulraheem Taofeeq; Abdulrazaq, Abdulkadir O. (Journal of Shariah Law Research, 2020)
Child marriage has generated a lot of argument among scholars and this no doubt culminated in promulgation of law on child right. One of the aims of this law is to prevent child marriage. Others include prevention of sexual abuse and other violent acts. There are divergences in the laws of various states as to marriageable age. The commutative effect of these various laws is that Nigeria as a country has taken a holistic approach to reduce child marriage but the issue is still persistence and it affects the health of children and their live beings. This paper therefore examines the concept of a child, the determinant factors for marriageable age of a child; whether the number or physical appearance is the contemplation of the law; as well as co-relation between child marriage and mortality. In doing this, the paper adopts doctrinal method which involves analysis of primary and secondary data. The paper argues that although child marriage has negative effect on the children, the determination of the word child is different under Shariah, because marriageable age is not based on numerical age alone; the physique of a child also an important feature.